2002
DOI: 10.1038/sj.onc.1205924
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of the APC/β-catenin pathway in endometrial cancer

Abstract: The activation of the APC/b-catenin signalling pathway due to b-catenin mutations has been implicated in the development of a subset of endometrial carcinomas (ECs). However, up to 25% of ECs have b-catenin nuclear accumulation without evidence of b-catenin mutations, suggesting alterations of other molecules that can modulate the Wnt pathway, such as APC, g-catenin, AXIN1 and AXIN2. We investigated the expression pattern of b-and g-catenin in a group of 128 endometrial carcinomas, including 95 endometrioid en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
165
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 223 publications
(183 citation statements)
references
References 49 publications
13
165
2
3
Order By: Relevance
“…CTNNB1 alterations in sinonasal HPC have been consistently reported in exon 3, with missense mutations [4,5]; mutations affecting positions 32-45 of the amino-terminal region disrupt phosphorylation-dependent degradation of b-catenin [6]. Numerous other tumor types harbor CTNNB1 mutations, most frequently desmoid-type fibromatosis [7,8] as well as salivary basal cell adenoma [9], pilomatricoma and pilomatrix carcinoma [10], hepatocellular carcinoma [11], colorectal carcinoma [12], medulloblastoma [13], endometrial adenocarcinoma [14], Wilms tumor [15], and adrenocortical carcinoma [16]. Sinonasal HPC shares the features of a uniform spindle and ovoid cell population and HPC-like vessels with SFT, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…CTNNB1 alterations in sinonasal HPC have been consistently reported in exon 3, with missense mutations [4,5]; mutations affecting positions 32-45 of the amino-terminal region disrupt phosphorylation-dependent degradation of b-catenin [6]. Numerous other tumor types harbor CTNNB1 mutations, most frequently desmoid-type fibromatosis [7,8] as well as salivary basal cell adenoma [9], pilomatricoma and pilomatrix carcinoma [10], hepatocellular carcinoma [11], colorectal carcinoma [12], medulloblastoma [13], endometrial adenocarcinoma [14], Wilms tumor [15], and adrenocortical carcinoma [16]. Sinonasal HPC shares the features of a uniform spindle and ovoid cell population and HPC-like vessels with SFT, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, published studies to date have not addressed the relationship between APC hypermethylation and protein expression. APC hypermethylation might cause transcriptional repression in tumors and cell lines of various origins, including CRC, lung, breast, and esophageal cancer, 11,22,23 they had suffered allelic losses at the APC locus. We demonstrated that de novo methylation alone does not influence APC expression in CRC, as the same percentage of tumors with and without allelic loss of the APC gene expressing APC were aberrantly methylated at the APC promoter.…”
Section: Discussionmentioning
confidence: 99%
“…6 In contrast, endometrioid endometrial carcinomas show microsatellite instability, 7 and mutations in the PTEN, 8 KRAS, 9 and CTNNB-1 genes. [10][11][12] Oncogenic activation of tyrosine kinases is a common mechanism of carcinogenesis. Tyrosine kinases play a role in transduction of proliferating signals and can be good therapeutic target in several tumors.…”
mentioning
confidence: 99%